Analisis Nilai Tambah Pengolahan Singkong Jarak Towo Menjadi Gethuk Frozen Di Ukm Gethuk Take Tawangmangu - Kusuma, Rahmalia Kartika; Marwanti, Sri; Sundari, Mei Tri (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Indonesia is a tropical country that has a lot of fertile agricultural land, so the production of agricultural commodities is also high. Cassava is one of the food crop commodities in the tuber category that can be used as raw material for an agroindustrial product. Jarak towo cassava is used as a raw material for the gethuk industry in Small and Medium Enterprises (UKM) Gethuk Take Tawangmangu. Processing cassava into frozen gethuk is one of the applications of added value to cassava commodities because during the production process additional costs are incurred so that the selling price is formed higher. This study aims to determine the costs, revenues, profits, business efficiency and added value from the business of processing cassava into frozen gethuk. This research used descriptive analysis basic method which is supported by survey method. The result of research are, total cost to produce the frozen gethuk in December 2021 was Rp148.286.358. Total revenue was Rp257.035.000 and Gethuk Take profit was Rp108.748.642. The value of R/C ratio is 1,73. The value added resulting from processing cassava into original gethuk dough is Rp9.186 with value-added ratio 54,1%, while the value added resulting from processing original gethuk dough into frozen gethuk original is Rp7.852 with value-added ratio 31,1%, value added from processing frozen gethuk with flavors is Rp8.266 with value-added ratio 32,1%, and value added from processing frozen gethuk with filling is Rp12.715 with value-added ratio 39,9%.